Analysis Of Green Human Resource Management Activities And Their Relationship With Sustainable Development Goals (Study On Pt Xyz Company Employees) - Rizal, Ghina Zahran; Sedyowidodo, Urip (Journal of Entrepreneurship, Management and Industry (JEMI), 2023)
The concept of Green Human Resource Management is expected to be a solution to these problems. This research was conducted to see the implementation of the GHRM concept in Company XYZ as a company engaged in the mining industry. There are several benchmarks, namely Green Training and Development and Green Performance Appraisals and Rewards, and observations of the implementation of goal 8 and goal 13 in SDG's points. Data was obtained by means of interviews with PT XYZ employees and also studies on secondary data sources. The results showed that there was an application of GHRM activities carried out by PT XYZ employees, but the company has not directly stated using the GHRM concept. SDG's activities have also been well implemented, in line with the company's objectives and also the implementation of GHRM